Initial Development of a Patient-Reported Experience Measure for Older Adults Attending the Emergency Department: Part II—Focus Groups with Professional Caregivers - Graham, B.; Smith, J.E.; Nelmes, P.; Squire, R.; Latour, Jos (2023)
A wide range of healthcare professionals provide care for patients in the emergency department (ED). This study forms part of a wider exploration of the determinants of patient experience for older adults in the ED, to assist the development of a new patient-reported experience measure (PREM). Inter-professional focus groups aimed to build on findings from earlier interviews with patients conducted in the ED, by exploring professional perspectives on caring for older people in this setting. A total of thirty-seven clinicians, comprising nurses, physicians and support staff, participated in seven focus groups across three EDs in the United Kingdom (UK). The findings reinforced that meeting patients’ communication, care, waiting, physical, and environmental needs are all central to the delivery of an optimal experience. Meeting older patients’ basic needs, such as access to hydration and toileting, is a priority often shared by all ED team members, irrespective of their professional role or seniority. However, due to issues including ED crowding, a gap exists between the desirable and actual standards of care delivered to older adults. This may contrast with the experience of other vulnerable ED user groups such as children, where the provision of separate facilities and bespoke services is commonplace. Therefore, in addition to providing original insights into professional perspectives of delivering care to older adults in the ED, this study demonstrates that the delivery of suboptimal care to older adults may be a significant source of moral distress for ED staff. Findings from this study, earlier interviews, and the literature will be triangulated to formulate a comprehensive list of candidate items for inclusion in a newly developed PREM, for patients aged 65 years and older.